Accumulation of MRI Markers of Cerebral Small Vessel Disease is Associated with Decreased Cognitive Function. A Study in First-Ever Lacunar Stroke and Hypertensive Patients - Huijts, Marjolein; Duits, Annelien; Van Oostenbrugge, Robert J.; Kroon, Abraham A.; De Leeuw, Peter W.; Staals, Julie (Frontiers in Aging Neuroscience, 2013)
Background – White matter lesions (WMLs), asymptomatic lacunar infarcts, brain microbleeds (BMBs) and enlarged perivascular spaces (EPVS) have been identified as silent lesions due to cerebral small vessel disease (cSVD). All these markers have been individually linked to cognitive functioning, but are also strongly correlated with each other. The combined effect of these markers on cognitive function has never been studied and would possibly provide more useful information on the effect on cognitive function. Methods – Brain MRI and extensive neuropsychological assessment were performed in 189 patients at risk for cSVD (112 hypertensive patients and 77 first-ever lacunar stroke patients). We rated the presence of any asymptomatic lacunar infarct, extensive WMLs, any deep BMB, and moderate to extensive EPVS in the basal ganglia. The presence of each marker was summed to an ordinal score between 0 and 4. Associations with domains of cognitive function (memory, executive function, information processing speed and overall cognition) were analyzed with correlation analyses. Results – Correlation analyses revealed significant associations between accumulating cSVD burden and decreased performance on all cognitive domains (all p≤.001). Results remained significant for information processing speed (r=-.181, p=.013) and overall cognition (r=-.178, p=.017), after correction for age and sex. Testing of trend using linear regression analyses revealed the same results. Discussion – We tested a new approach to capture total brain damage resulting from cSVD and found that accumulation of MRI burden of cSVD is associated with decreased performance on tests of information processing speed and overall cognition, implying that accumulating brain damage is accompanied by worse cognitive functioning.